An Analysis of the Use of Collaborative Learning Methods in Increasing Students’ Motivation in Learning English - Hasrianti; Andi Sadapotto; Lababa; Syahrir L; Sam Hermansyah (INTERACTION: Jurnal Pendidikan Bahasa, 2024)
This study aims to investigate the effectiveness of the collaborative learning method in enhancing students' motivation to learn English, focusing on seventh-grade students at SMPN 7 SATAP MAIWA. Employing a descriptive qualitative approach, the study explores how collaborative learning techniques influence students’ motivation and evaluates their role in improving the English learning process. The findings indicate that the collaborative learning method has a significant positive impact on students’ motivation. Among the 20 students who participated, 16 (80%) reported increased confidence in using English, opportunities to assist each other in overcoming challenges, and improved problem-solving skills when completing assignments. Group interactions further encouraged students to participate actively in learning activities, making the process more engaging and enjoyable. Collaborative learning also fostered stronger peer relationships and provided a supportive environment where students felt more comfortable expressing their opinions and ideas. The study concludes that the collaborative learning method is an effective strategy for boosting students' motivation in learning English. By working together in groups, students not only gain confidence in communication but also develop essential social and cognitive skills. This method encourages students to be more responsible for their learning while promoting mutual support and cooperation. Therefore, collaborative learning can serve as an alternative approach to improving the quality of English instruction, particularly in encouraging student-centered learning and active participation in the classroom.